Transformational Leadership in Digital Era: Analysis of Nadiem Makarim (Founder of GO-JEK Indonesia) Leadership Figure - Imelda Junita (Fakultas Ekonomi, Universitas Bangka Belitung, 2019)
Technology and internet has driven innovation and new opportunities by digitizing every customer, company, product, service, and process. In digital era, company has potential to touch all aspects of the business, including customers, employees, partners, business processes, and also global network of businesses and things from every industry around the world. Today, what will business leader do with digital business advantage has become a challange. The objective of this paper is to describe the concept of transformational leadership as a hallmark of future digital business leader. From evidence in literatures, in many successful organizations, transformational leaders have contributed to increase the effectiveness and performance of the organizations. By using descriptive method with phenomenological approach, the practice of transformational leadership of Nadiem Makarim as founder of GO-JEK Indonesia (an Indonesian-owned and run technology start-up that specialises in ride hailing, logistics, and digital payments) is examined. Then, this paper provides review about how Makarim’s leadership philosophy and practice has brought GO-JEK into success, Indonesia’s biggest start-up.